3D scanning and printing of a triathlon bike for performance improvement - Mahadeva, A.; Satyanarayana, S. B. (Chalmers Open Digital Repository, 2019)
This thesis is conducted at Chalmers University of Technology, Gothenburg within department of Industrial and Materials science. The project aims to develop a multi-purpose methodology for analysing and testing the developed prototype using a wind tunnel. Biking phase is considered in this thesis, since biking has the longest distance when compared to other phases. So, any small performance improvement in the biking phase will result in overall improvement. By performing an exploratory research and investigating the causes for performance improvement, methods such as rapid prototyping and reverse engineering are used. The project resulted in analysing the impact of mounted accessories at two different positions. Results obtained from the testing phase are presented in terms of coefficient of drag and power required by the rider to overcome a certain range of velocity.